Treatment of Adolescent Blount Disease Using Taylor Spatial Frame With and Without Fibular Osteotomy: Is There any Difference?. Issue 5 (July 2015) - Sachs, Ofer; Katzman, Alexander; Abu-Johar, Emad; Eidelman, Mark
Abstract : Background: In adolescents, Tibia Vara (Blount disease) patients usually present with combination of marked genu varum, procurvatum, and internal tibial torsion. When no growth remaining, standard treatment protocol for correction is osteotomy of the proximal tibia and fibula. In our study we compared 2 groups of patients: group A was treated with fibular osteotomy and group B was treated without fibular osteotomy. Methods: Twenty-three patients (25 tibias), 21 males and 2 females, mean age of 14.7 years (range, 13 to 21 y) were included in our study. All patients underwent correction with Taylor spatial frame. Group A (with fibular osteotomy) included 11 tibias and group B (no fibular osteotomy) included 14 tibias. Group A underwent correction by proximal tibial and fibular osteotomies (fibula was fixed distally by 2 ilizarov wires to the distal ring). Group B was treated by proximal tibial osteotomy only (fibula was not osteotomized and was not fixed to the tibia). Results: Correction goal was achieved in 9 cases in group A and 12 in group B. Mean time in frame was 15.9 weeks in group A and 14.14 in group B. Mean lengthening was 16.5 mm in group A and 12.8 mm in group B. Mean proximal tibia-fibula distance was 21.1 mm (group A) and 14.9 mm (group B). Mean distal tibia-fibula distance was 9.8 mm (group A) and 9.6 mm (group B). There was no ankle malalignment in both the groups. Complications included pin-tract infection in 11 patients and delayed union in 2 patients (1 in each group). Conclusion: We believe that in patients with minimal lengthening as needed in patients with adolescent Tibia Vara correction might be performed safely without osteotomy and fixation of the fibula. Level of Evidence: Level III.